Cognitive Dissonance in Health-Seeking Behavior of People in Indonesia to Prevent Covid-19 - Firda Ayu Kusuma Dewi Subagyo; Irwansyah Irwansyah (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
During the Covid-19 pandemic, many people experience cognitive dissonance, including in the process of seeking health. In the Covid-19 pandemic, people have to deal with various kinds of information, thoughts, and beliefs about Covid-19. Having a relevant but inconsistent cognition can create psychological discomfort or dissonance. The feeling of discomfort has made people try to seek health. Indonesian people’s health-seeking behavior is unique because of certain beliefs, information, perceptions, cultures, and unique environments in Indonesia. So, this study aims to analyze the cognitive dissonance process that occurs in Indonesian people's health-seeking behavior in the Covid-19 pandemic. This study is a literature study. We use secondary data of literary works, scientific journals, books, articles in the mass media, and statistical data as study objects. The results of this study indicate that the cognitive dissonance theory can be applied to answer the health-seeking behavior of Indonesian people in the Covid-19 pandemic. Many people in Indonesia choose traditional medicine to prevent Covid-19 because it is believed to be a natural treatment, has empirical evidence, and is easy to do independently. Many people in Indonesia choose traditional medicine because it is influenced by hereditary beliefs, culture, and also the variety of information they hold.